English: English - Irma Kharisma; Andi Ulfa Tenri Pada; Supriatno; Safrida; Ismul Huda (Postgraduate, University of Mataram, 2024)
Research to measure students' Critical Thinking Skills has been widely carried out in Indonesia. However, the development of Critical Thinking Skill measuring tools in Ecology using CBT is still limited. This study is part of research and development to develop a good instrument product for measuring students' Critical Thinking Skills. The question preparation format uses a two tier multiple-choice form. This study aims to prove the content validity of the Critical Thinking Skill instrument in Ecology Subject for Senior High School. Scale using Likert model and multiple-choice model with content validity coefficient based on expert assessments with Aiken’s formula. There are three experts who assess the items' relevancy, construction, and clarity using indicators of both scale formats. The results of the expert assessments are then used to calculate the coefficient of the validity with Aiken formula. The results showed that the content validity coefficient based on expert assessment on Likert format with Aiken formula is at 0.75-1.00 for each, while using the Aiken formula.